Efektifitas Pembelajaran IPS Menggunakan Strategi Jigsaw Pada Sub Bab Potensi Dan Sebaran Sumber Daya Alam Indonesia Siswa Kelas VII Di SMP N 1 Ngawen Kabupaten Klaten - Rismayanti, Dewi; , Dr. TjiptoSubadi, M. Si (2016)
This research was conducted in SMP Negeri 1 KlatenNgawen. The purpose of this study was to assess and describe: 1. The jigsaw strategy is more effective in achieving the learning objectives and the sub theme of the potential spread of Indonesian natural resources. 2. The difference in learning strategy and learning conventional jigsaw. This research includes experimental methods that research by studying an objective, systematic. Place of research conducted in SMP N 1 Ngawen Klaten, time studies over four days from 14-17 September 2015. The population of the entire students of class VII SMP N 1 NgawenKlaten.Variable of research free and bound. Data collection techniques there are 2 of tests and observation. No validity analysis techniques, rehabilitation, normality. No hypothesis analysis techniques to determine tingkat pemahamaan students. conclusions of this study (1) is more effective in the jigsaw strategy mencapai learning objectives at the sub theme of the potential and natural resources sewbran Indonesia. (2) The jigsaw strategy has better results than the conventional methods (lectures), although only slightly, but perbandinganya jigsaw strategy is more effective compared to conventional methods.